Corporate Compliance with Net-Zero Target and Environmental Regulations: Lessons from South Korea for Indonesia - Edy Lisdiyono; Nindya Dhaneswara; Rianmahardhika Sahid Budiharseno (APPTHI, 2025)
This study examines corporate compliance with net-zero emissions targets and environmental regulations in Indonesia and South Korea, with the aim of exploring lessons Indonesia can apply from South Korea's experience. The study uses a comparative, descriptive qualitative approach, with data collected through a review of legal documents, government regulations, corporate reports, scientific journals, and international publications. The analysis focuses on comparing Indonesia's voluntary compliance system, which still relies on fiscal incentives and non-sanction evaluations, with South Korea's mandatory compliance system through the Framework Law on Carbon Neutrality and Green Growth and the Korea Emissions Trading Scheme (K-ETS). The results show that South Korea's success in encouraging corporate compliance with net-zero is supported by a binding legal framework, integrated ESG reporting, and digital emissions monitoring. Meanwhile, Indonesia is still in the policy commitment stage. The study recommends strengthening the net-zero legal framework, integrating ESG-based reporting systems.